PROSES PRODUKSI TEPUNG BULU AYAM SEBAGAI BAHAN PAKAN SUMBER PROTEIN - , DESI ERLITA, Prof. Dr. Ir. Ali Agus, DAA., DEA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The uses of chicken feather waste to become as protein feed ingredients source hopefully may minimize the rate of pollution impact by chicken feather and lead a poultry farm with a friendly environment. A potential chicken feather as one component of the feed material is very good because of the poultry industry in Indonesia is thriving. One of the feed material terms is not a staple food. Ae average production of chicken feather is 6% of the life weight of the chicken. Broiler population in Indonesia in 2009 was 930.317.847, so produced chicken feather of 83.728.606/year. The objective of this research is make chicken feather meal as an alternative protein feed ingredients source. Analysis resulted in crude protein level of chicken feather meal of 80,97%, which is potential for feed ingredients. Chicken feather to be made as feed ingredients must be processed because containing keratin that cause hard to digest. Four methods of processing chicken feather into fodder ingredients are chemistry method, physical method, enzymatis method, or combination of these methods. This research used physical-chemical methods and enzymatis method. Physical-chemical methods were carried out with the addition of HCl and pressurized heating. If enzymatis method used papain enzym. From the analysis results obtained that the physical-chemical methods more rapidly in increasing protein level and protein indigestion compared to enzymatis method. Protein level and protein indigestion are best retrieved on treatment of 6 hours that is 88,96% and 30,57%. From economic analysis, the production of chicken feather meal as protein feed ingridients source deserve to be developed because it has a value of BEP 11.029,86 kg, Pay Back Period of 10 months, and BC Ratio 1,17.